Pandangan Positivisme dan Post-Positivisme dalam Filsafat Ilmu Mempengaruhi Pendekatan dalam Linguistik Terapan - Luwiti, Sri Rumiyatiningsih (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
This article explores the important role of the positivism and post-positivism paradigms in the development of research methods and approaches in the field of applied linguistics. Positivism emphasizes objective measurements, empirical data, and quantitative methods, such as word frequency analysis and language standard tests. In contrast, post-positivism, which developed as a reaction to positivism, recognized the limitations of absolute objectivity and introduced more flexible and contextual approaches, such as critical discourse analysis and ethnography in language learning. Through this study, the author shows that although these two paradigms are different, they can be combined to obtain a more comprehensive understanding of language phenomena. This collaboration allows researchers to explore the meaning of language in a broader socio-cultural context, while maintaining an objective aspect of measurement. The results of this study are expected to contribute to the development of a more holistic research methodology in applied linguistics.